Legal Thoughts Regarding Joint Assets in Legal Institutions in Indonesia - Sitti Mashitah Tualeka; Oyo Sunaryo Mukhlas (al-Afkar, Journal For Islamic Studies, 2023)
The dissolution of marriage has legal consequences on marital property, namely the termination of joint assets. However, in its development, cases related to the division of joint assets often give rise to various perceptions in classifying disputed objects as joint assets or not, such as disputed objects in the form of insurance coverage, funeral expenses, and pension funds. This paper focuses on the theme of the legal status of insurance coverage, funeral expenses, and pension funds in relation to joint assets. The conclusion of this research is that there are differences in the status of insurance coverage, funeral expenses, and pension funds in relation to joint assets. If the premiums are paid during the marriage, the assets will become joint assets, as stated in Article 35 paragraph (1) of Law Number 1 of 1974 concerning Marriage. On the other hand, if the premiums are paid before the marriage, even if the person concerned enters into a marriage, the insurance coverage, funeral expenses, and pension funds, as stated in Article 35 paragraph (2) of Law Number 1 of 1974 concerning Marriage, will remain as the individual's separate property.